Analysing passengers' behaviours when boarding trains to improve rail infrastructure and technology. (June 2019) - Oliveira, Luis CR; Fox, Catherine; Birrell, Stewart; Cain, Rebecca
Highlights: Concentrated boarding was proved by video recording of 581 rail passengers. Passengers tend to board trains through doors within 24 m of the platform entrance. Design and technology could motivate passengers to board trains using other doors. Evenly distributed boarding can reduce dwell time. Abstract: Concentrated boarding describes the phenomenon when rail passengers congregate in certain areas of the platform and board the train carriages that stop near these areas. This influences the distribution of passengers throughout the carriages, which can negatively affect passenger comfort, safety at the platform-train interface, efficiency of the rail network, and the reputation of rail travel as a whole. This project aimed to determine whether concentrated boarding occurs in stations in the UK in order to understand its relevance for future rolling stock, infrastructure design and its associated manufacturing research. Video recording technology was used to observe the movements of passengers in Oxford Station and data was collected for nine individual trains. By reviewing the recordings, the number of passengers boarding through each door of the trains was determined, and the boarding distribution along the length of the platform was plotted. Several reasons for noted trends are offered, and potential solutions proposed. The use of real time information could be invaluable to minimise concentrated boarding, as it would allow passengers to make informed decisions as to where they could board trains to have a better journey experience. These findings indicate the relevance of a human-centred design process, particularly the user research stages, in the process of defining priorities for manufacturing and engineering.